2022
DOI: 10.3390/ani12202768
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Dam Age on Lifetime Productivity of Angus Replacement Beef Females

Abstract: Comprehensive cow-calf production data was utilized to evaluate the impact of dam age on lifetime productivity of Angus replacement beef females. Cows used in this study were commercial Angus replacement females born between 2006 and 2020, ranging in age from 1 to 14-yr of age (n = 3568). To determine the impact of dam age on lifetime productivity, cows were classified by age groups, specifically 2-, 3-, 4-, 5-, 6/7-, and 8-yrs old and older. The 8-yr and older group consisted of females that were up to 14-yr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Upon analyzing the data presented in Table 5 , it is noteworthy that the studied groups of cows with different genotypes exhibited the distribution of the relationships “live weight × measurements” and “live weight × score for the overall assessment of the exterior”, based on the characteristics of the degrees of the heritability coefficient for the studied productive traits [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Upon analyzing the data presented in Table 5 , it is noteworthy that the studied groups of cows with different genotypes exhibited the distribution of the relationships “live weight × measurements” and “live weight × score for the overall assessment of the exterior”, based on the characteristics of the degrees of the heritability coefficient for the studied productive traits [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the impact of cow age on lifetime productivity of female offspring it has been found that calves born to five-year-old (or older) Angus cows had increased productivity compared to those born to four-year-old (or younger) dams [ 44 ]. When investigating the effect of calving period on the lifetime reproductive performance and productivity of Angus cows in Canada it has been concluded that heifers calving early vs calving later in their first calving season had increased pregnancy rates and weaned more calves [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes were strongly affected by the number of times a cow failed to wean a calf and suggested breed affects cow longevity. Culling for failure to maintain an annual calving interval can markedly reduce observed longevity but confounds reproductive success with true longevity (MacNeil & Vukasinovic, 2011; Wellnitz et al., 2022).…”
Section: Introductionmentioning
confidence: 99%